SOCIAL FACTORS AND ALCOHOL CONSUMPTION: STATE OF THE ART AND DIRECTION FOR FUTURE WORK - Rubiah, Ajan; Vivien Wong Chin, Yew; Abdul Hair, Awang (2020)
Alcohol consumption is increasing global and it is the reasons for large number of death. This study reviews the literature to find the predictors and provide direction for future work. A review of 17 articles was conducted. The findings showed that most of studies were conducted in Europe followed by US. There are limited number of reviewed studies and the predictors are mainly related to socio-economic status, social factors, social networking sites, and stress. More studies are needed to understand the predictors.